Foreign Exchange Volatility and Corporate Risk Mitigation Approaches: Evidence from Indonesian SMEs - Nasriani , Ira (Yayasan Sinergi Kawula Muda, 2024)
Foreign exchange (FX) risk management is crucial for firms operating in global markets, as currency fluctuations can significantly impact financial performance. This study explores the key determinants influencing firms' hedging decisions, the role of managerial characteristics, and the effectiveness of hedging strategies. Employing a qualitative approach, data were collected through in-depth interviews with financial executives and risk managers. The findings indicate that firms with higher foreign debt exposure and liquidity constraints are more likely to hedge against FX risks. Additionally, managerial risk aversion plays a critical role in determining hedging behavior, aligning with agency theory predictions. Furthermore, the study highlights the importance of integrating both financial and operational hedging strategies to optimize FX risk management. While large firms have better access to sophisticated hedging instruments, SMEs face significant challenges in managing FX exposure due to resource limitations. The study suggests that policymakers should enhance access to hedging tools for SMEs to improve financial resilience. These findings contribute to the existing literature on FX risk management by providing empirical evidence on the interplay between firm-specific factors, managerial characteristics, and hedging effectiveness. Future research should consider longitudinal studies to examine the dynamic nature of FX risk exposure and assess the long-term impact of hedging practices on firm performance.